2013
DOI: 10.1353/hpu.2013.0170
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perceived Cultural Sensitivity of Health Care Office Staff and Its Association with Patients’ Health Care Satisfaction and Treatment Adherence

Abstract: Research suggests that patients' interactions with their front desk office staff and patient-centered culturally sensitive health care are important factors in diverse patients' overall health care satisfaction. Yet, patient-centered culturally sensitive health care research has focused almost exclusively on provider care. This study tested the hypothesis that patient-perceived cultural sensitivity of front desk office staff has a significant positive association with patient treatment adherence and that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Cultural knowledge also involves “learning about other cultures’ worldview, languages and the elements of culture, such as historical, political, social and economic factors” (Suh, , p. 194); (v) cultural sensitivity which is both a cognitive and affective component of cultural competency. It involves attitudes, perceptions and values that show heightened awareness of one’ own culture and recognition of and respect for another's culture (Brisco, ; Harper, ; Horvat et al, ; Kleiman, ; Lucas et al, ; Stanhope et al., ; Tayab & Narushima, ; Wall, Tucker, Roncoroni, Allan, & Nguyen, ). Cultural sensitivity in the community health setting involves an understanding of cultural similarities and differences in how people perceive health and illness and how they communicate with health providers (Burnard, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural knowledge also involves “learning about other cultures’ worldview, languages and the elements of culture, such as historical, political, social and economic factors” (Suh, , p. 194); (v) cultural sensitivity which is both a cognitive and affective component of cultural competency. It involves attitudes, perceptions and values that show heightened awareness of one’ own culture and recognition of and respect for another's culture (Brisco, ; Harper, ; Horvat et al, ; Kleiman, ; Lucas et al, ; Stanhope et al., ; Tayab & Narushima, ; Wall, Tucker, Roncoroni, Allan, & Nguyen, ). Cultural sensitivity in the community health setting involves an understanding of cultural similarities and differences in how people perceive health and illness and how they communicate with health providers (Burnard, ).…”
Section: Resultsmentioning
confidence: 99%
“…The first consequence is perceived quality healthcare by clients when healthcare providers demonstrate cultural competence (Harmsen et al, 2005;Harper, 2006;Lucas et al, 2008;May & Potia, 2013;Tayab & Narushima, 2015;Wade & Bernstein, 1991). The second consequence is adherence to treatment and advice when there is cultural competence (Harmsen et al, 2005;Horvat et al, 2014;Ishikawa et al, 2014;Majumdar et al, 2004;May & Potia, 2013;Owiti et al, 2014;Wade & Bernstein, 1991;Wall et al, 2013). The third consequence is satisfaction when clients perceive the health provider incorporates cultural perspectives (Dunagan, Kimble, Gunby, & Andrews, 2014;Foronda, 2008;Garneau & Pepin, 2015;Harmsen et al, 2005;Lucas et al, 2008;May & Potia, 2013;Owiti et al, 2014;Stanhope et al, 2008;Tayab & Narushima, 2015;Wall et al, 2013).…”
Section: Antecedents and Consequences Of Cultural Competencementioning
confidence: 99%
“…Also, this type of caring enhances human dignity, comfort and independence of the patient . Studies indicate that enacting cultural sensitivity in health care has positive effects on patient outcomes including decreasing stress in the nurses taking care of patients , reducing postpartum depression and stress in mothers , decreasing depression and social isolation in the patients receiving primary care services , improvement in quality of life in different racial and ethnic groups and increasing satisfaction and adherence to treatment .…”
Section: Resultsmentioning
confidence: 99%
“…The night shift nurse reported the child's health condition to the head nurse during the work shift change and stated: 'During medication, I found that the father of this child has three wives'. The head nurse immediately said: 'This is true that polygamy may common among Balochi culture, but this is rather nice to not judge others at all' (Field note 5 nurses taking care of patients (37), reducing postpartum depression and stress in mothers (38), decreasing depression and social isolation in the patients receiving primary care services (39), improvement in quality of life in different racial and ethnic groups (40)(41)(42) and increasing satisfaction and adherence to treatment (12,28,30,35,42,43).…”
Section: Aspects Of Culturally Sensitive Carementioning
confidence: 99%
“…Another study that included 1602 participants found that treatment satisfaction could explain a 10% variance in the patients' treatment adherence. [23] All quotes were assessed using a 11-point Likert scale, where 0 corresponds to 'I agree very much' and 10 corresponds to 'I disagree very much'. IBD: inflammatory bowel disease; IQR: interquartile range.…”
Section: Discussionmentioning
confidence: 99%